Silicon Dioxide in Active Food Packaging: A Review on Mesoporous Carriers for Encapsulated Antioxidants and Antimicrobials - Pratama, Bima Putra; Khairullah, Aswin Rafif; Maruf, Ilma Fauziah; Kurniasih, Dea Anita Ariani; Khalisa, Andi Thafida; Wardhani, Bantari Wisynu Kusuma; Mustofa, Imam; Mulyati, Sri; Ludfiani, Dini Dwi; Putra, Endo Pebri Dani; Pangestuti, Martasari Beti; Galia, Meta Aquarista; et al. (Trends in Sciences, 2025)
The increasing demand for packaging technologies that actively maintain food quality and safety has highlighted the potential of silicon dioxide (SiO₂) as a multifunctional material. This review discusses the physicochemical properties, mechanisms of action, application formats, functional performance, and regulatory aspects of SiO₂ in active food packaging. Amorphous and mesoporous forms of SiO₂ exhibit high surface area, strong adsorption capacity, and thermal stability, enabling their use as moisture and oxygen absorbers as well as carriers for antimicrobial and antioxidant compounds. Reported applications include silica gel sachets for moisture control, coatings and films reinforced with nanosilica, and mesoporous silica nanoparticles (MSNs) for controlled release of bioactive agents. Experimental evidence demonstrates that these systems can effectively reduce microbial growth, delay fruit ripening, and slow lipid oxidation, thereby extending shelf life while maintaining sensory quality. At the same time, nanosilica raises safety concerns due to potential migration and bioaccumulation, prompting stricter toxicological testing and regulatory oversight by bodies such as FDA, EFSA, and BPOM. The main finding of this review is that amorphous and mesoporous SiO₂ consistently provide superior functionality compared to crystalline forms, while regulatory compliance and consumer acceptance remain key challenges. Overall, SiO₂ shows strong promise as a safe and effective active packaging component, with future opportunities in smart and biodegradable packaging innovations. HIGHLIGHTS Silicon dioxide (SiO2) offers multifunctional advantages in food packaging, including moisture and oxygen absorption, antimicrobial activity, and antioxidant delivery. The material’s high surface area, stability, and biocompatibility make it highly effective for extending food shelf life and improving safety. This review provides a comprehensive synthesis of SiO2 applications, mechanisms, and regulatory perspectives, offering clear guidance for future research and industrial adoption. GRAPHICAL ABSTRACT